2011
DOI: 10.1093/rheumatology/ker327
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia differentially affects IL-1 -stimulated MMP-1 and MMP-13 expression of fibroblast-like synoviocytes in an HIF-1 -dependent manner

Abstract: Hypoxia in arthritic joints may differentially affect the IL-1β-stimulated expression of MMP-1 and MMP-13 in rheumatoid synovial fibroblasts. This effect is dependent on HIF-1α expression. This hypoxia-mediated differential effect should be taken into consideration when testing the efficiency of therapies that target HIF-1α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 30 publications
0
27
2
Order By: Relevance
“…With increasing time, expression of MMP-1 increased (34). However, the expression of MMP-13 was markedly decreased in the current study.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…With increasing time, expression of MMP-1 increased (34). However, the expression of MMP-13 was markedly decreased in the current study.…”
contrasting
confidence: 55%
“…Previous studies have revealed that expression of MMP-1 and MMP-13 in cartilage and synovium were significantly higher than those of control group (34). With increasing time, expression of MMP-1 increased (34).…”
mentioning
confidence: 88%
“…Consistent with our data in TB, hypoxia and HIF-1α regulate MMP-driven tissue destruction in hypoxic fibroblasts within rheumatoid synovium. 36 In summary, we show for the first time that human TB lesions are severely hypoxic. Hypoxia increases MMP-1 gene expression and secretion during M.tb infection, and M.tb infection independently increases HIF-1α activity even under conditions of normoxia.…”
Section: Discussionmentioning
confidence: 60%
“…Other proteases observed to be increased included collagenase 3, that is increased in expression in NFkB mediated inflammation in mammals [82-84] and during vitellogenesis induced muscle atrophy in salmonids [43]. Angiotensinogen, the precursor of both angiotensin I & II, was also increased in expression, and is known to interfere with the actions and production of IGF-I, which in mammals is mediated by the NFκB pathway in collaboration with protein kinase C [85,86].…”
Section: Discussionmentioning
confidence: 99%